A comparative analysis of graduate preparedness for a career in General Internal Medicine before and after national subspecialty recognition to inform curricular changes: have we met the mark? - Halman, Samantha; Tran, Allen; O'Brien, Tara; Card, Sharon (Canadian Medical Education Journal, 2023)
Background: A survey of General Internal Medicine (GIM) graduates published in 2006 revealed large training gaps that informed the development of the first national GIM objectives of training in 2010. The first recognized GIM certification examination was written by candidates in 2014. The landscape is again changing with the introduction in 2019 of competency-by-design (CBD) to GIM training. This study aims to examine pre-existing and emerging training gaps with standardization of GIM curricula and identify new training needs to inform CBD curricula. Methods: GIM graduates from all 16 Canadian programs from 2014 -2019 were emailed a survey modeled after the original study published in 2006. Graduates were asked about their preparedness and importance ratings for various elements of practice. Results: Many of the previously identified gaps (difference between importance and preparedness ratings) have been resolved in specific clinical areas (obstetrical and perioperative medicine) and skills (exercise stress testing) although some still require ongoing work in areas such as substance use disorders. Importantly, gaps still exist in preparedness for some intrinsic roles (e.g. managerial skills). Conclusions: The development of a national GIM curriculum has helped close some educational gaps but some still exist. Our study provides data needed to meet the evolving needs of our graduates.